Pengaruh Berbagi Pengetahuan (Knowledge Sharing) dalam Peningkatan Perilaku Keselamatan Pelayaran - Hendrawan, Andi; Sasongko, Aris; Pramono, Sri (Marine Science and Technology Journal, 2022)
Unsafe conditions can cause chronic work stress that will interfere with the performance of Kabal's subordinates (ABK). Guaranteed occupational safety and health will certainly improve performance which in turn will increase work productivity. The purpose of this research is to prove whether there is an effect of knowledge sharing on shipping safety. The research method was carried out using the analytical survey method. The results show that there is an effect of sharing knowledge on shipping safety with a value of P = 0.00.